2014
DOI: 10.1038/cddis.2014.77
|View full text |Cite
|
Sign up to set email alerts
|

Two combined photosensitizers: a goal for more effective photodynamic therapy of cancer

Abstract: Photodynamic therapy (PDT) is a clinically approved therapeutic modality for the treatment of diseases characterized by uncontrolled cell proliferation, mainly cancer. It involves the selective uptake of a photosensitizer (PS) by neoplastic tissue, which is able to produce reactive oxygen species upon irradiation with light, leading to tumor regression. Here a synergistic cell photoinactivation is reported based on the simultaneous administration of two PSs, zinc(II)-phthalocyanine (ZnPc) and the cationic porp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 44 publications
3
103
0
1
Order By: Relevance
“…173 Different photosensitizers create direct damage localized on the plasma membrane, lysosome, mitochondria, Golgi apparatus, endoplasmic reticulum, and nuclear membrane, and this localization appears to influence the type of cell death. 4,130 The extent of the effect of the tissue microenvironment and other cellular inputs, however, remains unclear. 36 Damage to tumor cells leads to the release of cell-death-associated molecular patterns (CDAMs) and damage-associated molecular patterns (DAMPs), which in turn attract leukocytes such as dendritic cells and neutrophils, thus producing an acute inflammatory response.…”
Section: Mechanism Of Actionmentioning
confidence: 98%
“…173 Different photosensitizers create direct damage localized on the plasma membrane, lysosome, mitochondria, Golgi apparatus, endoplasmic reticulum, and nuclear membrane, and this localization appears to influence the type of cell death. 4,130 The extent of the effect of the tissue microenvironment and other cellular inputs, however, remains unclear. 36 Damage to tumor cells leads to the release of cell-death-associated molecular patterns (CDAMs) and damage-associated molecular patterns (DAMPs), which in turn attract leukocytes such as dendritic cells and neutrophils, thus producing an acute inflammatory response.…”
Section: Mechanism Of Actionmentioning
confidence: 98%
“…The use of combination strategies is also aimed at achieving higher impact at lower doses of each drug, thus avoiding the usual serious side effects, such as those linked with chemotherapy. A synergistic effect in killing cancer cells was found by combining two photosensitisers in PDT, zinc(II)-phthalocyanine and meso-tetrakis(4-Nmethylpyridyl)porphine (Acedo et al 2014).…”
Section: Combination Strategies In Pdtmentioning
confidence: 99%
“…A 1996 report showed that PDT sequentially directed against lysosomes and mitochondria could result in enhanced photokilling in a mouse sarcoma model [21]. Another report indicated a similar result when lysosomal and golgi were the PDT targets [22]. A potential mechanism for this result has been suggested: lysosomal photodamage can release calcium stores [23] which, in turn, activate the protease calpain leading to cleavage of ATG5 to a pro-apoptotic fragment [24].…”
Section: Introductionmentioning
confidence: 99%